2020
DOI: 10.1177/0011000020934518
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Wellness Among Latinx Immigrants: Meaning in Life, Belonging, and Hope as Mediators

Abstract: This study examined a conceptual model depicting the direct and indirect relationships between attachment insecurity, state hope, belongingness, meaning in life (MIL), and three wellness indicators (i.e., life satisfaction, physical health, and depression) of first-generation Latinx immigrants in the United States. Results of structural equation modeling analysis showed adequate model fit with the data from a sample of 288 individuals. The final model indicated that the link between comfort-seeking attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
9
0
1
Order By: Relevance
“…Empirical research has found the positive effects of belongingness among Hispanics/Latinx (Yoon et al, 2012 ). For instance, it was found that having a strong group ethnic identity and sense of belongingness can protect their psychological wellbeing against the detrimental impact of perceived discrimination and other adverse interpersonal circumstances (Cobb et al, 2019 ; Shelton et al, 2020 ). Importantly, the desire to group belongingness and social connectedness with peers and adults in an extrafamilial context such as school or neighborhood is particularly salient during adolescence, as individuals begin to explore who they are and how they fit in the social world (Brown & Larson, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has found the positive effects of belongingness among Hispanics/Latinx (Yoon et al, 2012 ). For instance, it was found that having a strong group ethnic identity and sense of belongingness can protect their psychological wellbeing against the detrimental impact of perceived discrimination and other adverse interpersonal circumstances (Cobb et al, 2019 ; Shelton et al, 2020 ). Importantly, the desire to group belongingness and social connectedness with peers and adults in an extrafamilial context such as school or neighborhood is particularly salient during adolescence, as individuals begin to explore who they are and how they fit in the social world (Brown & Larson, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…These experiences may differ from Latinx students in PWIs. In addition, in the existing literature, there is an exclusive or majority sampling of Mexican and Mexican American participants in Latinx studies (e.g., Corona et al, 2020; Ojeda et al, 2014; Shelton et al, 2020; Vela et al, 2014). It is important to note that Latinx is a diverse group and while they may share similar cultural values, each group may vary due to factors such as immigration, colonization, and sociogeopolitical history.…”
Section: Discussionmentioning
confidence: 99%
“…La investigación de la esperanza en niños, niñas y adolescentes (NNA) ha aumentado exponencialmente en los últimos años dada su alta asociación con el bienestar general 1,2 . Pese a ello, en Chile, las investigaciones relacionadas a la esperanza en infancia son escasas.…”
Section: Introductionunclassified